2017
DOI: 10.1111/1759-7714.12424
|View full text |Cite
|
Sign up to set email alerts
|

Extent of visceral pleural invasion and the prognosis of surgically resected node‐negative non‐small cell lung cancer

Abstract: BackgroundVisceral pleural invasion (VPI) is generally considered a poor prognostic factor in non‐small cell lung cancer (NSCLC). VPI is defined as penetration beyond the elastic layer of visceral pleura (PL1), including the visceral pleural surface without the involvement of adjacent structures (PL2) by cancer cells. The aim of this study was to evaluate the influence of the extent of VPI on NSCLC prognosis.MethodsThis was a retrospective study of 90 patients with resected node‐negative NSCLC with VPI. The ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…However, their study had several limitations, including a limited number of patients who underwent sublobectomy, relatively few outcome events, and a short follow-up due to their data being extracted from the SEER program (2017 update). In contrast to their study, data on the extent of VPI (PL1 and PL2) were not collected in our study for the survival analysis because data were not available before 2010 in the SEER database; however, several studies have confirmed that the extent of VPI may not influence survival outcomes in patients with completely resected NSCLC with VPI (11,23,24). Moon et al (12) studied the surgical outcomes of 89 NSCLC patients with VPI (N=38) or lymphovascular invasion (N=71) and showed that the OS rate did not differ significantly by the surgical extent (P=0.615), and sublobar resection was not an independent risk factor according to the multivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
“…However, their study had several limitations, including a limited number of patients who underwent sublobectomy, relatively few outcome events, and a short follow-up due to their data being extracted from the SEER program (2017 update). In contrast to their study, data on the extent of VPI (PL1 and PL2) were not collected in our study for the survival analysis because data were not available before 2010 in the SEER database; however, several studies have confirmed that the extent of VPI may not influence survival outcomes in patients with completely resected NSCLC with VPI (11,23,24). Moon et al (12) studied the surgical outcomes of 89 NSCLC patients with VPI (N=38) or lymphovascular invasion (N=71) and showed that the OS rate did not differ significantly by the surgical extent (P=0.615), and sublobar resection was not an independent risk factor according to the multivariate analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Second, we did not classify VPI as PL1 or PL2. Pleural invasion can be classified into four groups: PL0, PL1, PL2, and PL3 ( 20 ). Among them, PL1 and PL2 are considered VPI in the current TNM staging system.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that VPI does not significantly impact OS in patients with early-stage NSCLC (106). Building upon this finding, Seok et al (107) conducted a retrospective study in 2017, examining the survival of 90 patients with N0 NSCLC and concurrent VPI. Ultimately, they concluded that the extent of VPI may not affect the prognosis of N0 NSCLC patients who undergo surgical resection with VPI.…”
Section: Visceral Pleural Invasion and Prognosis And Survivalmentioning
confidence: 99%